PENGARUH PEMBERIAN JUICE BUAH NAGA TERHADAP PENINGKATAN HEMOGLOBIN - Nelly Mariati; Wulandari Wulandari; Mirawati Mirawati (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2022)
Nutrition has a big role in determining maternal health. Malnutrition of pregnantwomen is not only related to malnutrition in the developing fetus, but also directly affectsmaternal health and the risk of maternal death. There are two critical pathways by whichmaternal nutrition can affect fetal survival, namely anemia and calcium deficiency. Anemia inpregnant women contributes as much as 20% of maternal deaths and low calcium consumptioncan lead to gestational hypertension which can trigger preeclampsia and eclampsia, which arethe second most common cause of maternal death. Handling anemia by consuming plants suchas vegetables and fruits, one of which is dragon fruit. Dragon fruit contains highphytochemicals, namely flavonoids 7.21 mg CE/100 grams. In addition, dragon fruit is a fruitthat is rich in antioxidants and relatively high calcium and iron which plays a good role in boneand blood function. The purpose of this study was to analyze the effect of dragon fruit juice onincreasing Hb levels in pregnant women. The research method used is Quasi Experiment (quasi-experimental) with pre-test post-test group design. The sampling technique of this research wasdone by purposive sampling, obtained a sample of 30 respondents consisting of 15 respondentsfrom the intervention group and 15 respondents from the control group. The results showed thatthere was an effect before and after being given dragon fruit juice, the test used a paired t testwhere it was obtained for the intervention group p value 0.001 and for the control group p value0.011.The intervention administration of Fe tablets and dragon fruit juice increased the Hb levelof pregnant women by 1.42 g/dl, while the administration of Fe tablets only gave an increase of1.2 g/dl.